Anti-Inflammatory Small Molecules To Treat Seizures and Epilepsy: From Bench to Bedside. (June 2016) - Dey, Avijit; Kang, Xu; Qiu, Jiange; Du, Yifeng; Jiang, Jianxiong
Abstract : As a crucial component of brain innate immunity, neuroinflammation initially contributes to neuronal tissue repair and maintenance. However, chronic inflammatory processes within the brain and associated blood–brain barrier (BBB) impairment often cause neurotoxicity and hyperexcitability. Mounting evidence points to a mutual facilitation between inflammation and epilepsy, suggesting that blocking the undesired inflammatory signaling within the brain might provide novel strategies to treat seizures and epilepsy. Neuroinflammation is primarily characterized by the upregulation of proinflammatory mediators in epileptogenic foci, among which cyclooxygenase-2 (COX-2)/prostaglandin E2 (PGE2 ), interleukin-1β (IL-1β), transforming growth factor-β (TGF-β), toll-like receptor 4 (TLR4), high-mobility group box 1 (HMGB1), and tumor necrosis factor-α (TNF-α) have been extensively studied. Small molecules that specifically target these key proinflammatory perpetrators have been evaluated for antiepileptic and antiepileptogenic effects in animal models. These important preclinical studies provide new insights into the regulation of inflammation in epileptic brains and guide drug discovery efforts aimed at developing novel anti-inflammatory therapies for seizures and epilepsy. Trends: Unresolved inflammation in the brain is a common feature in epilepsy, and is primarily characterized by elevated proinflammatory mediators in epileptogenic foci. Blocking excessive inflammatory processes in the brain increases the seizure threshold and reduces the likelihood of recurrent seizures, thereby providing disease prevention or modification. Anti-inflammatory therapeutics represent a complementary strategy to the current symptomatic treatments. Small molecules that specifically target the proinflammatory mediators are realistic candidate agents for anti-inflammatory therapeutics owing to their advantages in production, delivery, and pharmacokinetics. Future efforts to develop novel therapeutics for epilepsy will aim to identify novel anti-inflammatory small molecules with potential to be moved from bench to bedside.